(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
In this period of emergency, the lockdown, which is necessary to prevent the spread of the virus, is affecting social rights and putting a strain on the population, both individually and collectively. Among the various possible perspectives of analysis, here are proposed some anthropological-legal reflections on social rights, proximity and solidarity.